Language Shift of Assilulu Language Among Adolescence in Assilulu Village, Leihitu District, Central Maluku Regency - Talanggera, Asti Asmi; Rumalean, Iwan (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Language shift occurs from one language to the next, or to a language that is not displaced by other dialects. Local language is one of the parts of culture, but it is also a method of communication utilized by society to connect socially with each other. Language has numerous social roles, especially social communication, social regulation, and social cooperation. The function of language in communication is to send messages. Based on initial observations done by the author in Assilulu village, Leihitu sub-district, Central Maluku Regency, it was observed that practically all teenagers aged 12-17 do not know the Assilulu language. Thru a sociolinguistic study with a phenomenological method, this paper will detail the variables underlying the change from the usage of regional language to Indonesian (Ambon Malay) in communication in Assilulu Village. The population of this study is all teenagers living in Assilulu Village. The research sample was taken randomly. Data was acquired by observation or listening methods and interviews. Based on the research conducted in 2022, several factors were found to cause this language shift, including: the family's level of education, the choice of straightforward and polite language within the family, the family's age, the family's social stratification, the lack of regional language learning for the family, the family's residential area, and the family's attitude toward language. The Indonesian language used in family communication in Assilulu Village is dominated by Ambon Malay.